2018
DOI: 10.1007/s40333-018-0062-6
|View full text |Cite
|
Sign up to set email alerts
|

Potato absorption and phytoavailability of Cd, Ni, Cu, Zn and Pb in sierozem soils amended with municipal sludge compost

Abstract: Effects of sludge utilization on the mobility and phytoavailability of heavy metals in soil-plant systems have attracted broad attention in recent years. In this study, we analyzed the effects of municipal sludge compost (MSC) on the solubility and plant uptake of Cd, Ni, Cu, Zn and Pb in a soil-potato system to explore the mobility, potato plant uptake and enrichment of these five heavy metals in sierozem soils amended with MSC through a potato cultivation trial in Lanzhou University of China in 2014. Ridge r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…As a result of application of sewage sludge, Cd content in potato tubers increased 4-fold, and an increase in the content of the remaining metals varied from 21% (Zn) to 96% (Pb). Studies by many authors evidenced the contribution of the application of sewage sludge to an increase in the content of heavy metals in plants, often in amounts exceeding acceptable values (Liu et al, 2018;Yang et al, 2018;Antonious, 2020;Buta et al, 2021;Eid et al, 2021;Kołodziej et al, 2023). Manure, in turn, is considered as a fertiliser that poses no threat for the environment in terms of content of heavy metals.…”
Section: Yielding and Chemical Composition Of Plantsmentioning
confidence: 99%
“…As a result of application of sewage sludge, Cd content in potato tubers increased 4-fold, and an increase in the content of the remaining metals varied from 21% (Zn) to 96% (Pb). Studies by many authors evidenced the contribution of the application of sewage sludge to an increase in the content of heavy metals in plants, often in amounts exceeding acceptable values (Liu et al, 2018;Yang et al, 2018;Antonious, 2020;Buta et al, 2021;Eid et al, 2021;Kołodziej et al, 2023). Manure, in turn, is considered as a fertiliser that poses no threat for the environment in terms of content of heavy metals.…”
Section: Yielding and Chemical Composition Of Plantsmentioning
confidence: 99%
“…Bioconcentration factor (BCF) or Bio‑accumulation factor is an indicator that evaluates the ability of vegetables to absorb heavy metals in plant tissues [22] , [23] , [24] . Several studies determined the BCF in vegetables such as Khan et al [25] ; Liu et al [26] ; Jalali et al [27] who reported BCF values greater than 1 for Cd, Cu, Zn, Ni and Pb in Solanum tuberosum ; Ju et al [28] , Jalali and Meyari [29] reported high values in edible leafy and root vegetables; Eliku and Leta [30] , Jolly et al [31] in leafy and non-leafy vegetables reported low BCF values. BCF values greater than 1 indicate that plants are enriched with heavy metals, and it is a risk to human health because these metals can enter the food chain based on their mobility and bioavailability in the soil [32] .…”
Section: Introductionmentioning
confidence: 99%
“…In light of these challenges, the second approach involves the integration of GMLS data. Many scholars have explored different spectral processing methods encompassing spectral pre-processing techniques such as Savitzky-Golay (SG) smoothing [15], SNV [16], multiplicative scatter correction (MSC) [17], first-order differential reflectance (FD) [18], and second-order differential reflectance (SD) [19]. Additionally, spectral selection methods such as principal component analysis (PCA) [20], competitive adaptive reweighted sampling (CARS) [21], UVE [22], and successive projections algorithm (SPA) [23] have been employed.…”
Section: Introductionmentioning
confidence: 99%